What is the role of stereotactic ablative radiotherapy in the management of surgically resectable and operable stage I non-small cell lung cancer? - Love, Susannah M.; Hardman, Gillian; Mashar, Ruchir; Shah, Rajesh D. (Journal of Thoracic Disease; Vol 9, No 5 (May 28, 2017): Journal of Thoracic Disease, 2017)
The use of stereotactic ablative radiotherapy (SABR) with the intention to cure stage I non-small cell lung cancer (NSCLC) in preference to surgical resection is currently a contentious and hotly debated topic. It may even be claimed that SABR could impact the future management of lung cancer in the same way that percutaneous coronary stents impacted the management of ischemic heart disease.